History of madness in the present: the ways of assistence and the psychiatric reform in the ststeof Parana (Tempo e Argumento, 2009)
They are scarce in Brazil historiographical studies on the madness and its correlative as the assistance, institutions, knowledge and practices that exceed the mark of thirty years of the twentieth century. When it emphasizes the specific history of psychiatric social services, in addition to few studies that discuss in the field of history, the latest phase this process that is corresponded to movement of Psychiatric Reform, also there aren’t studies about the specifics of the motion over on of the federation units. Given this premise is main goal this article, historicizing the nuances this process in the state of Parana. For this, initially it was contextualized the process of reform at the national level and then we highlight an important aspect of the trajectory of psychiatric social services in the state until the conduct of the movement for reform.
Keywords: madness; psychiatric social services; psychiatric reform